A sacrococcygeal teratoma-a rare entity among adult males: a case report and review of literature - Khan, Suhail M.; Khan, Azhar A.; Kanth, Anzeen N.; Khan, Aymen M.; Kanth, Irfita N. (International Surgery Journal, 2021)
Sacrococcygeal teratoma (SCT) is derived from embryonic germ cell layers and is one of the commonest tumours in infants. It is the most commonly occurring solid congenital tumours in the foetus and the new born. It is very rare in adults with less than a hundred cases documented in literature, with even rarer cases of male presentation. We report a case of a 26-year-old adult male presenting with a sacrococcygeal teratoma who was treated in our hospital along with its literature review.